Coalition-Preclusion Contracts and Moderate Policies - Hans Gersbach; Maik T. Schneider; Oriol Tejada (ETH Zurich, CER-ETH - Center of Economic Research, 2014)
We examine the effects of a novel political institution, which we call Coalition- Preclusion Contracts, on elections, policies, and welfare. Coalition-Preclusion Contracts enable political parties to credibly commit before the elections not to form a coalition after the elections with one or several other parties specified in the contract. We consider a political game in which three parties compete to form the government and study when contracts of the above type will be written. We find that in most circumstances Coalition-Preclusion Contracts with a single-party exclusion rule defend the interests of the majority by moderating the policies implemented. Moreover, they yield welfare gains for a large set of parameter values. We discuss the robustness of the results in more general settings and study how party-exclusion rules have to be adjusted when more than three parties compete in an election.
Keywords: D72; D82; H55; 330; coalition formation; political contracts; elections; government formation